PERILAKU PEMBELIAN NASABAH PADA APLIKASI PEGADAIAN DIGITAL PERAN MODERASI LITERASI DIGITAL DAN BRAND TRUST - Sherly Ernawaty Susanto; Inijilia Wulan Gratia; Lidya Djuwita Pratiwi Canon (JURNAL ILMIAH EDUNOMIKA, 2026)
The rapid growth of digital financial services in Indonesia has accelerated the adoption of digital pawn platforms, including the Pegadaian Digital application. This study examines the influence of perceived ease of use, perceived usefulness, perceived risk, and security on customer purchasing decisions, with digital literacy and brand trust as moderating variables. Employing a quantitative explanatory research design, data were collected from 200 respondents via purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results confirm that perceived ease of use (β=0.287; p=0.000), perceived usefulness (β=0.314; p=0.000), and security (β=0.241; p=0.000) positively and significantly influence purchasing decisions, while perceived risk exerts a significant negative effect (β=–0.198; p=0.001). Moreover, brand trust significantly moderates the negative effect of perceived risk on purchasing decisions (β=0.183; p=0.001), and digital literacy strengthens the positive effect of perceived ease of use on purchasing decisions (β=0.214; p=0.000). The model demonstrates substantial predictive power, explaining 67.3% of the variance in purchasing decisions (R²=0.673). These findings contribute to the advancement of digital consumer behavior theory in the financial technology sector and offer practical recommendations for Pegadaian to enhance its digital service quality and user-centric strategy